Rajasthan Playing to its Strengths : A Strategy for Sustained and Inclusive Growth - World Bank (World Bank, Washington, DC, 2018)
India’s largest state by area, Rajasthan also stands out in economic performance and achieved a greater reduction in poverty than any other low income state. This strong performance reflects broad-based efforts towards policy reform across sectors that resulted in a more productive and diversified agriculture sector, higher investments in manufacturing, and substantial improvements in public service delivery. These achievements notwithstanding, Rajasthan still lags behind many other states in India. The state is also among the lower performers in womens’ and girls’ education and gender gaps have shown little improvement over the years. Rajasthan is now at a crossroads and faces serious challenges for sustaining rapid and inclusive growth. In recent years, growth has slowed down and the crucial tourism sector has lost market share. A worsening water crisis is making traditional agricultural practices increasingly unsustainable, while growing fiscal pressures, due partly to deficiencies in the electricity sector, are narrowing the fiscal space available to implement comprehensive policy actions. The purpose of this report is to help develop a possible growth strategy as part of the ongoing dialogue with the state. In particular, the report is expected to serve as important input to the Bank’s lending strategy for the state going forward by proposing an overall strategic framework for the development of the state.